Neo-adjuvant platinum-based chemotherapy followed by chemoradiation and radical surgery in locally advanced cervical cancer (Lacc) patients: A phase II study. Issue 7 (July 2018) - Ferrandina, Gabriella; Palluzzi, Eleonora; Gallotta, Valerio; Gambacorta, Maria Antonietta; Autorino, Rosa; Turco, Luigi Carlo; Macchia, Gabriella; Cosentino, Francesco; Gui, Benedetta; Mattoli, Maria Vittoria; Ronzino, Graziana; Valentini, Vincenzo; et al.
Abstract: Purpose: The aim of this Phase II, non-randomized study was to assess activity and safety of neoadjuvant chemotherapy (NACT) before chemoradiation (CT/RT) followed by radical surgery (RS) in locally advanced cervical cancer (LACC) patients. Methods and materials: The primary end point was rate of pathologic complete response (pCR). FIGO Stage IB2-IVA patients were administered NACT chemotherapy (paclitaxel 80 mg/m 2, carboplatin AUC 2), for 6 weeks, followed by Intensity Modulated Radiotherapy plus simultaneous boost (total dose of 50.4 Gy to CTV1, and 39.6 Gy to CTV2). Clinical response was assessed according to RECIST criteria. Responsive patients were triaged to RS. The regimen would be considered active if >20 pCRs were registered in 39 patients. Results: 45 patients were enrolled into the study; 25 patients (55.5%) were FIGO stage IIB, 9 cases (20.0%) had stage III disease. At work up, pelvic lymph node involvement was documented in 38 (84.4%) patients; pCR was documented in 18 out of 40 patients (45.0%). Grade 3–4 hematological toxicity after NACT occurred in 4 patients; CT/RT associated grade 3 toxicity was found in 7 patients. Early and late postoperative complications were detected in 16, and 11 cases, respectively. Three-year PFS and OS were 66.0% and 86.0%, respectively. Conclusions: NACT followed by CT/RT by IMRT and RS, is feasible and safe; failure to achieve the primary endpoint has to be recognized; however, enrollment of a higher rate of poor prognosis patients compared to historical data used to calculate sample size, could have resulted in reduced activity.